2022
DOI: 10.3390/ijerph19084684
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Drug and Substance Use among Malaysian Youth: A Nationwide Survey

Abstract: Uncontrolled drug and substance use (DSU) may pose unprecedented threats to nation building and a country’s socioeconomic development. Despite considerable efforts made and resources used to address DSU concerns, Malaysia has seen a significant annual rise in cases of DSU. The bulk of the reported cases originate from youth between the ages of 15 and 40 years. To date, data related to DSU in Malaysia have been entirely dependent on operation statistics, arrest counts, and reported cases; DSU may therefore be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Between 2022 and 2023, there were two publications reporting data on kratom use collected through nationwide surveys conducted in Malaysia [63 ▪▪ ,64 ▪▪ ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Between 2022 and 2023, there were two publications reporting data on kratom use collected through nationwide surveys conducted in Malaysia [63 ▪▪ ,64 ▪▪ ].…”
Section: Resultsmentioning
confidence: 99%
“…In the national Drug and Substance Use (DSU) survey conducted in Malaysia between January 2020 and July 2021 among persons 15–40 years old, 2.8% responders reported lifetime prevalence of kratom ( M. speciosa ) use, and 1.5% responders reported kratom use within the past 30 days of being surveyed [63 ▪▪ ]. A secondary analysis of 2019 data collected through the National Health and Morbidity Survey (NHMS) enrolling a total of 10 472 Malaysians aged 18 years and older reported 0.40% (95% CI 0.22–0.56%) rate of kratom use within the past 30 days of being surveyed, and that individuals reporting kratom use also had a high probability of reporting the use of other substances [64 ▪▪ ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite having some information pertaining to polysubstance use in Malaysia, existing studies are limited to specific populations such as injection drug users [ 23 , 24 ], prisoner [ 25 ], and men who have sex with men (MSM) [ 26 ]. The study on polysubstance use at the national level was only reported among adolescent (aged 13–17 years) [ 27 ] and youth (15–40 years) [ 28 ]. Therefore, it is necessary to investigate a nationally representative sample of the adult population to provide information for the development of theories explaining the pattern of polysubstance use.…”
Section: Introductionmentioning
confidence: 99%
“…According to the statistic, around 126,390 addicts were identified during the period of 5 years from 2016 to 2020. Relapse rates for the period of five years showed an average of 29.4% of the overall cases detected (National Anti-Drugs Agency, n.d., 2021) In dealing with the growing problems of substance use disorders, the need for a better and more effective intervention to treat this disorder is extremely high (Ismail et al, 2022;Ting Chie et al, 2016). Many researchers in the field of behavioural change have made numerous studies to better understand and contribute to more effective interventions in the field of substance use disorders.…”
Section: Introductionmentioning
confidence: 99%